Sistem IT Bank BSI Sering Trouble: Analisis Sentimen Netizen di Aplikasi X - Sururi, Miftahus (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2024)
This study analyzes netizen sentiment towards Bank Syariah Indonesia (BSI) on application X, specifically on complaints and responses related to service disruptions, security issues, and management. The data shows that the majority of sentiment is negative, with the main complaints regarding disruptions to payment services, cash withdrawals, e-wallet top-ups, and mobile banking. In addition, sharp criticism was directed at customer data security management due to ransomware attacks. Recruitment issues that were considered not based on quality also added to the negative perception of this bank. However, there were positive responses related to social initiatives such as waqf fundraising, which received appreciation from users. Neutral sentiment emerged from informative comments and users in areas with limited banking alternatives who still chose BSI. This study concludes that BSI needs to improve its technology and security infrastructure, as well as respond quickly to customer service and data issues. With these improvements, BSI is expected to increase customer trust and loyalty in the future.